Theories of educational leadership and management - Bush, Tony (London SAGE Publications Ltd, 2020)
"This fifth edition of Tony Bush’s bestselling text explores the links between educational management theories and the main models of leadership, and their application to policy and practice globally across varied educational contexts.

This fully updated new edition is informed by an enhanced global perspective and expanded coverage of important contemporary issues including teacher leadership, professional learning communities, transformational leadership, instructional leadership and a critical assessment of distributed leadership.

This is essential reading for all teachers who aspire to management, as well as for experienced leaders on Masters’ level courses, and for those studying school management as part of education degrees."
Chapter 1: The Importance of Leadership and Management for Education -- Chapter 2: Models of Educational Leadership and Management -- Chapter 3: Formal Models -- Chapter 4: Collegial Models -- Chapter 5: Political Models -- Chapter 6: Subjective Models -- Chapter 7: Ambiguity Models -- Chapter 8: Cultural Models -- Chapter 9: Conclusion.
Includes bibliographic references and indexes.
Keywords: School management and organization. -- Great Britain; Organizational behavior. -- Great Britain; Educational leadership -- Great Britain; Management -- Great Britain